Pediatric anesthesia training to early career stage: Opportunities for firm foundations. Issue 1 (6th August 2020) - Munshey, Farrukh; McDonnell, Conor; Matava, Clyde
Abstract: Attaining professional contentment can be challenging for many. Academic success, psychosocial support, and the confidence to provide excellent clinical care at the workplace are key pillars that can help build a sense of meaning in a career. The role of mentorship in facilitating these key pillars at different stages of pediatric anesthesia training and new independent practice is instrumental. For mentees aspiring for a career in pediatric anesthesia, there are several points of focus. Mentees should seek out mentors early in training, build on these relationships, and explore opportunities for peer mentorship as they advance in their career. For mentors, introducing mentees to the clinical and academic aspects of pediatric anesthesia and setting the foundation for the mentee to advance in their career can be both gratifying and stimulating. In this article, we explore the development and progression of a mentor‐mentee relationship through training to the early career stage and its role in developing a meaningful career in pediatric anesthesia.